An investigation into passenger satisfaction with in-flight catering on domestic services of the South African Airways - Mills, Sandra Margaret (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. in Home Econ.) -- University of Stellenbosch, 1988.